2016
DOI: 10.12659/msm.898231
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1 (PON1) rs662 Polymorphism and Its Association with Serum Lipid Levels and Longevity in the Bama Zhuang Population

Abstract: BackgroundThe present study was performed to identify the association of PON1 rs662 polymorphism with serum lipid levels and human longevity in the Bama Zhuang population.Material/MethodsPON1 genotypes were determined by Taqman SNP Genotyping Assays in 110 long-lived inhabitants (longevity group, aged 90–110 years), 110 healthy inhabitants in Bama County (control 1 group, aged 43–82 years) and 110 healthy inhabitants in Nandan County (control 2 group, aged 28–82 years) without family history of longevity.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Several centenarians at the same period belong to a large family, suggesting that longevity is closely related to genetics. This conjecture was validated in series of subsequent studies [ 11 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 56%
“…Several centenarians at the same period belong to a large family, suggesting that longevity is closely related to genetics. This conjecture was validated in series of subsequent studies [ 11 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 56%
“…LDL peroxidation product increases when PON1 is of low level, resulting in an excess of reactive oxygen species, causing imbalance between antioxidant system and oxidant system. Studies have reported the significance of PON1 in diagnosing CRC in European populations, and revealed the relationship between PON1 gene polymorphism and PON1 enzyme activity [14,15]. However, research on the significance of PON1 and the combination of PON1 and commonly used biomarkers CEA, CA12-5, CA19-9 to diagnose CRC in Chinese population is still unclear.…”
Section: Ivyspringmentioning
confidence: 99%
“…Diets and lifestyles were different in these different populations. Diets and lifestyles are similar to those described in our previous article [ 40 ]. Keeping this in mind, we can identify the genes related to blood lipids and suggest eating a healthy diet to reduce the impact of hyperlipidemia on people’s health.…”
Section: Discussionmentioning
confidence: 86%